Limfadenitis KronikGranulomatosa Profil Klinikopatologik Limfadenitis Kronik Granulomatosa Tuberkulosis dan non-Tuberkulosis di Departemen Patologi Anatomik FKUI-RSCM Periode Tahun 2018-2022 - Nurlia Erdian, Defi; Harahap, Agnes Stephanie; Ham, Maria Francisca (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2025)
Background Chronic granulomatous lymphadenitis (CGL) is an inflammatory condition associated with lymphoproliferative lesions, infections, and autoimmune diseases. One of the etiologies of CGL is Mycobacterium tuberculosis (MTB). According to WHO data in 2020, Indonesia still ranks third globally for TB cases. To ensure appropriate patients’ treatment, there is a need to accurately diagnose TB lymphadenitis through clinicopathological. Therefore, this research aimed to determine the clinicopathological features that differentiate TB lymphadenitis from other types. Method This research was a retrospective analytical review and data were collected from the Department of Anatomic Pathology archives, Faculty of Medicine, University of Indonesia/Dr. Cipto Mangunkusumo Hospital for 5 years, from 2018 to 2022. Clinical data were obtained from electronic medical records. The histopathological assessment involved evaluating the presence of polymorphonuclear cells (PMN), datia cells, and central necrosis in CGL. Result A total of 156 CGL cases were identified, with 63.8% of TB lymphadenitis patients being female and the highest age group was <45 years. No significant association was found between age, a history of autoimmune diseases, malignancy, and TB lymphadenitis. The most commonly involved lymph node location was in the colic area, with a proportion of 62.2%. There was a significant association between lymph node location and the occurrence of TB lymphadenitis (p<0.003). Other variables assessed included the presence of PNM cells (81.7%), datia cells (94%), and central necrosis (88.8%), with p-values <0.000 for each variable. The results showed a significant association between PMN cells, datia cells, and central necrosis with TB lymphadenitis. Conclusion The characteristics of the female gender, lymph node location, presence of PMN cells, central necrosis, and datia cells could be considered as features to assess for diagnosing CGL caused by MTB.